Islamic Religious Education as Student Character Development in the Millennial Era - Firman, Firman (Universitas Syiah Kuala, 2024)
The millennial phenomenon becomes very interesting when faced with the condition of Islamic education in Indonesia. On the one hand, Islamic education has a target and orientation to create perfect human beings. However, on the other hand, at the same time, Islamic education must be able to develop the skills, abilities, potential and behavior of its followers in responding to internal challenges and the challenges of the global world that has opened wide before us.